Propuesta de Clasificación Microclimática en función a la Vegetación predominante en la Cuenca del Rio Itaya, Loreto-Perú. - Tello y Cols., Diana (2019)
Classify a type of climate is a challenge in medium and low forest where variations occur only under the influence of the growth of cities or deforestation processes and therefore the selection of climates methodologies are not sufficient to define microclimas [1]. So, the main objective of the research was to implement a proposed micro-level according to the predominant vegetation type in the Itaya River basin, which is flanked by two major rivers Amazon and Nanay. We worked with 47 weather stations were located inside and outside the study area. Thermohygrometers were used for monitoring digital sampling points. The methodology used was based on Thornthwaite (1949) [2], it was available for the monthly values of evapotranspiration, precipitation and temperatures of 35 consecutive series. To make the proposal to complement micro-level variables were recorded as thermal range, minimum temperature and relative humidity. Determining a total of 19 microclimates. The results show that the microclimates depend on the type of vegetation, especially aguajales type where there are fewer of microclimates and are homogeneous, while in hills dominate over thermal fluctuations and finally heterogeneous deforested areas there are a variety of microclimates heterogeneous to their environment. So this climate classification system complementary to the traditional methodology for characterizing micro-climates in the lowlands.